The Association Between Smoking and Health-Related Quality of Life Among Chinese Individuals Aged 40 Years and Older: A Cross-Sectional Study - Cheng, Xi; Jin, Chenggang (Frontiers in Public Health, 2022)
Objective: The purpose of this study was to investigate the association between smoking and health-related quality of life among Chinese individuals aged 40 years and older. Method: Using a stratified multistage sampling method, data from 1543 adults aged 40 years and older were obtained from a household survey conducted in eight provinces in China. The health-related quality of life was quantified based on the utility index obtained using a standardized instrument entitled “The European Five-Dimensional Health Scale (EQ-5D-5L)”. Descriptive statistics were used to summarize the demographic characteristics and social factors of the sample according to smoking status. An instrumental variable (IV) probit model was used to estimate the association between smoking status and health-related quality of life. Results: Of the 1543 participants, 485 (31.43%) were smokers and 1058 (68.57%) were nonsmokers. Smoking was negatively associated with the probability of having a higher quality of life (p<0.01). For smokers, the average probability of having a higher quality of life was 11.65% lower than when they did not smoke. Conclusions: These findings suggest that smoking reduces health-related quality of life among Chinese individuals aged 40 years and older. Anti-smoking programs should consider this factor.